Impact of environmental education on environmental quality under the background of low-carbon economy - Wu, Ye; Wan, Jiawei; Yu, Wen (Frontiers in Public Health, 2023)
Introduction How does environmental education affect environmental quality? There is no consensus among theorists. This paper is devoted to exploring the influence mechanism of environmental education and environmental quality under the background of a low-carbon economy from a theoretical model and empirical analysis. Methods The research method of this paper includes two aspects. First, from the consideration of the central planner, this paper draws on and improves the Ramsey Model to explore the interaction mechanism among environmental education, environmental quality and green growth. Second, this paper uses provincial panel data from China from 2011 to 2017 for empirical analysis, which mainly verifies the impact mechanism of environmental education on environmental quality. Results and discussion The theoretical model shows that environmental education enhances green consumption intention through residents' environmental awareness and enhances enterprises' cleaner production motivation through environmental pressure. Correspondingly, the pressure to improve environmental quality will also promote the economy's endogenous growth through the digital economy's transformation and the accumulation of human capital. The empirical analysis confirms that environmental education can improve environmental quality through green consumption and pollution control. Still, the effect of improving environmental quality only through pollution control is not apparent, and pollution control needs to be combined with environmental education, especially in high-pollution areas. Finally, this paper puts forward some suggestions for optimizing environmental education.